Podas de mantenimiento durante diferentes épocas del año en la producción de cacao ( Theobromacacao L.) Clonal CCN-51 en el Cantón Buena Fe - Yantalema Gáleas, William Henán (2013)
The present investigation was carried out in the enclosure Deep" "Puddle in the property "Three Siblings" in a plantation of cocoa CCN-51 established seven years of age to full exhibition solar entrance to it dams it inside Dribble 11 km located in the km. 52 via BuenFé. Sto. Domingo County of Ríos. Their geographical location is: latitude 00° 29' South and a longitude of 79° 21' West. With an altitude of 220 m.s.n.m. During the dry time 2012 and the rainy time 2013. The investigation consisted on evaluating the effects of maintenance prunings during different times of the year, in the production of cocoa (Theobroma cocoa L.) clonal CCN - 51en the Canton Good Faith. The treatments consisted on T0 (witness) with monthly deschuponamiento the whole year, / / T1 with a pruning a year + elimination of 60 foliage%, / / T2 with two prunings a year November and March + elimination of 50 foliage%, / / T3 two prunings a year Julio and January + elimination of 40 foliage%, / / T4 with two prunings a year Julio and January + elimination of 20 foliage%, / / T5 with three prunings a year June, October and February + elimination of 20 foliage%. You uses an experimental design "Totally at random" with (DCA) 6 treatments and 4 repetitions, and 6 useful plants for parcel. After taking data during the year from June 2012 until May 2013 the intensity of Floración, intensity of Brotación, intensity of Cherelles Wilt was evaluated, incidence of Broom of Witch, I number of Healthy Ears, I number of Sick Ears, Index of Ear, Index of Seed, Fresh Weight in kilograms, Dry Weight in kilograms hectare a year, and the test was applied from Tukey to 95% of probabilities to determine significant differences among the treatments. All the treatments presented a bigger intensity of Floración, in the months of April and May. For Intensity of Brotación likewise were all the treatments they demonstrated bigger intensity in the month of March. The presence of fruits attacked by Cherelles Wilt was lightly superior in the treatment T5 with three prunings a year June, October and February + elimination of 20 foliage% in the month of January. The presence of vegetative witch's broom that I reach the biggest average was the treatment T2 with two prunings a year November and March + elimination of 50 foliage%, in the month of March. The one that obtained the biggest production of healthy ears was the treatment T1 with a pruning a year + elimination of 60 foliage%, with an average of 185,49 ears. The treatment T2 with two prunings a year November and March + elimination of 50 foliage% was the one that present the biggest quantity in sick ears, with an average of 286,74 ears. Although statistically all the treatments were same.